The twilight saga. New moon [videorecording (DVD)] - Weitz, Chris, 1969-; Stewart, Kristen, 1990-; Pattinson, Robert, 1986-; Lautner, Taylor, 1992-; Burke, Billy; Sheen, Michael; Fanning, Dakota, 1994-; Lutz, Kellan, 1985-; Kendrick, Anna; Greene, Ashley, 1987-; Facinelli, Peter, 1973-; Reaser, Elizabeth, 1975-; et al. (Summit Entertainment, 2010)
Bella is still very much in love with Edward, but ancient secrets threaten to destroy them. Edward decides to leave Forks, Washington to keep Bella safe. Bella tempts fate to get a glimpse of Edward and is saved from the brink by Jacob. Something is happening to Jacob that he can't explain to Bella, and their friendship starts to deteriorate. When Alice returns to tell her that Edward thinks she is dead, Bella must go on a journey to save Edward.